Prosecuting International Crimes and Human Rights Abuses Committed Against Children Leading International Court Cases - Grover, Sonja C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This casebook addresses selected precedent-setting rulings of various international human rights and international criminal courts with a focus on the child victims of international crimes and human rights abuses. The cases are analyzed from a children$1 (Bs human rights perspective and the question is examined as to what extent the international courts are according these children justice.s
An Introduction to the Organizational Structure, Enabling Statutes or Conventions, Case Processing Procedure, and Jurisdiction of the International Courts -- The Inter-American Human Rights System -- European International Human Rights Court System -- The International Ad Hoc Criminal Courts of Rwanda and the Territory of the Former Yugoslavia -- The Special Court of Sierra Leone -- The International Criminal Court -- The International Human Rights Courts -- Inter-American Court of Human Rights -- European Court of Human Rights -- The International Ad Hoc Criminal Courts -- International Criminal Tribunal for Rwanda -- International Tribunal for the Prosecution of Persons Responsible for Serious Violations of International Humanitarian Law Committed in the Territory of Former Yugoslavia Since 1991 -- The International Hybrid Criminal Courts -- The Special Court for Sierra Leona -- The Special Court for Sierra Leona -- The International Criminal Court (The Hague) -- Case 9: The Prosecutor v. Thomas Lubanga Dyilo (Democratic Republic of the Congo).
Keywords: Law; Law; International Criminal Law; Human Rights; International Humanitarian Law, Law of Armed Conflict